Implementation of Min Max Algorithm as Intelligent Agent on Card Battle Game - Silvester Dian Handy Permana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
Information technology brings transformation from the physical world into the digital world. This transformation developed in various fields, especially games. In the past, games that are involving physical objects such as chess, cards, dominoes, and mahjong are popular for the publics. Card battle game is a game that pits strength between 2 cards. The game must have 2 players who will compete. However, if a player wants to practice before the match or wants to play alone, he needs Non Player Character (NPC). The NPC will be the opponent in card battle games. In order for NPCs to be able to fight players, a special algorithm is needed to make the NPCs compete with players. The algorithm that can be implemented into the NPC is the Min Max Algorithm. This algorithm is a responsive algorithm which can count every step of the player. The results of this study are expected to provide suitable opponents for players who want to practice or compete in Card Battle Game on their own.